Electrical Safety in the farm: Case Study Research at Michigan USA 2010 - Fathurrahman Fathurrahman (PTE FTK UIN Ar-Raniry, 2018)
Electrical safety concern has been rise from early utilization of electricity. This report is about electrical accident that took place in one agricultural farm in Michigan, USA in summer 2010. A bilingual Latino farm worker (28) was electrocuted in a 6000-acre potato farm when he touched one of tower of self-propelled central pivot irrigators, which is irrigating the farm at that time. The delta corner-grounded system is used at the farm. The multicultural environment is also escalated the risk.